MAKNA SESAJI DAN NILAI PENDIDIKAN KARAKTER PADA TRADISI PETIK LAUT DI DESA BINOR DALAM PERSPEKTIF ETNOLINGUISTIK - Naimatul Jannah; Linda Eka Pradita; Doni Uji Windiatmoko (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
. The results showed that there were 16 offerings of the Sea Picking tradition peeled with lexical, grammatical, and cultural meanings and there were The purpose of this study is to describe the lexical meaning, grammatical meaning, and the cultural meaning of offerings and the value of character education contained in the Petik Laut tradition. This type of research is a qualitative research with ethnolinguistic approach and the value of character education. The data source and data of this research are the tradition of Sea Pickingeight character education values ??contained in the Petik Laut tradition. Keywords: Ethnolinguistics, Karkater Education Values, Tradition of Petik Laut